ANALYSIS OF EMPLOYEE PERCEPTION ABOUT THE WHISTLEBLOWING SYSTEM TOWARD INTENTION TO CONDUCT WHISTLEBLOWING - Faris Adilah; Icuk Rangga Bawono; Warsidi Warsidi (Fakultas Ekonomi, Universitas Bangka Belitung, 2020)
This research is entitled “Analysis of Employee Perception about the Whistleblowing System toward Intention to Conduct Whistleblowing (The Study on Employees of Purbalingga and Purwokerto Tax Office)”The objective of this research is to examined individual factors that can influence intention to conduct whistleblowing by applying the Theory of Planned Behavior, namely behavioral attitudes, subjective norms and perceived behavioral on the employees of the Purbalingga Tax Office and employees of Purwokerto Tax Office. This research was conducted at the Purbalingga Tax Office and Purwokerto Tax Office. Using variable that explain in Theory of Planned Behavior, the result of this study can be conclude that: (1) there is positive effect of behavioral attitude toward the intention of employee to conduct whistleblowing, (2) there is positive effect of subjective norm toward the intention of employee to conduct whistleblowing information, and (3) there is positive effect of perceived behavioral control toward the intention of employee to conduct whistleblowing.